The Resistance Mechanisms and Clinical Impact of Resistance to the Third Generation Cephalosporins in Species of Enterobacter cloacae Complex in Taiwan - Chung-Yu Chang; Po-Hao Huang; Po-Liang Lu (MDPI AG, 2022)
Enterobacter cloacae complex (ECC) is ubiquitous in the environment and is an important pathogen causing nosocomial infections. Because routine methods used in clinical laboratories cannot identify species within ECC, the clinical significance of each species within ECC is less known. We applied hsp60 gene sequencing to identify the species/clusters of ECC and detected β-lactamase genes and class 1 integrons with PCR for 184 clinical ECC isolates in Taiwan from 2013 to 2014 to investigate the clinical impact of species within ECC. The four most common clusters were E. hormaechei subsp. steigerwaltii (cluster VIII) (29.9%), E. hormaechei subsp. oharae (cluster VI) (20.1%), E. cloacae subsp. cloacae (cluster XI) (12%), and E. kobei (cluster II) (10.3%). E. hormaechei, which consisted of four clusters (clusters III, VI, VII, and VIII), is the predominant species and accounted for 57.1% of the isolates. The ceftazidime resistance rate was 27.2%, and the ceftriaxone resistance rate was 29.3%. Resistance to third generation cephalosporin was associated with a higher 30-day mortality rate. In total, 5 (2.7%), 24 (13.0%), and 1 (0.5%) isolates carried ESBL, AmpC, and carbapenemase genes, respectively. Class 1 integrons were present in 24.5% of the isolates, and most of the cassettes pertain to antibiotic resistance. Resistance to third generation cephalosporins, multidrug resistance, and class 1 integrons were significantly more in E. hormaechei (clusters III, VI, VII, and VIII) than in the other species. The 30-day mortality rate and 100-day mortality did not differ significantly between patients with E. hormaechei and those with infections with the other species. In conclusion, the distribution of third generation cephalosporin resistance, multidrug resistance, and class 1 integrons were uneven among Enterobacter species. The resistance to third generation cephalosporins possessed significant impact on patient outcome.